solve the following quadratic equation for x √6x+7-(2x-7)=0 Question solve the following quadratic equation for x √6x+7-(2x-7)=0 in progress 0 Math Faith 1 month 2021-08-21T13:17:23+00:00 2021-08-21T13:17:23+00:00 1 Answer 0 views 0

## Answers ( )

Answer:Step-by-step explanation:Hi,

Sqrt (6x +7) – (2x – 7 ) = 0

sqrt ( 6x + 7 ) = ( 2x – 7 )

———————-Squaring both side———————————–

( sqrt ( 6x + 7 ))^2 = ( 2x – 7 )^2

6x + 7 = 4x^2 -28x +49

0 = 4x^2 -28x -6x +49 – 7

4x^2 -34x +42 = 0

Divide each term with 2

2x^2 – 17x +21 = 0

2x^2 – 14x – 3x +21 = 0

2x ( x – 7 ) – 3( x – 7 ) = 0

( x – 7 ) ( 2x – 3 ) = 0

x – 7 = 0 or 2x – 3 = 0

x = 7 or 2x = 3

x = 7 or x = 3/2